PEMETAAN POTENSI KERAWANAN BENCANA LONGSOR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN SOJOL - Sholihah, Wilda Ismiatus; Arif, Nursida (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
Sojol Subdistrict, Donggala Regency, Central Sulawesi, is located on the Pacific Ring of Fire, dominated by steep hills, sandy loam soil, and variable rainfall, making it highly prone to landslides. This study maps landslide vulnerability potential using Geographic Information System (GIS) technology through overlay with five weighted scoring criteria: slope gradient (DEMNAS), land cover, rainfall (CHIRPS), soil type, and rock type. Geological data and land cover data were processed using ArcGIS 10.8. The results of the study show that the landslide vulnerability level of Sojol Sub-district is divided into three classes: low, moderate, and high. Villages with high landslide risk levels are Siboang, Bou, and Balukang, characterised by steep slopes (>70%), sparse dryland forest vegetation, and clay rock types that are highly susceptible to erosion during the rainy season. The landslide hazard map can be used as a basis for disaster mitigation, spatial planning, and raising public awareness of landslide risks.